Ethnomedical Use, Phytochemistry, Nutritional Profile, Commercial Potential, and Other Potential Applications of Psidium guajava (Guava) - Limenew Abate Worku; Meseret Zebeaman; Rakesh Kumar Bachheti; Archana Bachheti; Yashwant S. Rawat; Azamal Husen; Rahel Gebeyehu Shiferaw (Journal of Food Quality)
Psidium guajava (Family: Myrtaceae) is a well-known fruit in tropical and subtropical areas of nations such as India, South America, Bangladesh, Indonesia, and Pakistan. This study seeks to provide a thorough overview of the pharmacological characteristics, phytochemistry, nutritional profile, ethnomedical use, and possible applications of P. guajava. Several databases, including PubMed, Web of Science, Scopus, and ScienceDirect, served as the primary data sources for this study. Different parts of this plant, fruit, pulp, peel, seeds, leaves, bark, and oil, are rich in bioactive phytochemicals, which are responsible for various biological activities as well as for the synthesis of nanoparticles. The fruit of P. guajava has been used to produce processed food items such as juice, cake, puree, jelly, jam, toffee, pickles, and wine. The leaf extract has also been used to heal wounds with swollen gums, cough, diarrhea, and oral ulcers. Iron, calcium, phosphorus, vitamins A and C, and minerals are abundant in P. guajava fruit. The fruit, seed, leaf, and peel of P. guajava are rich in organic and inorganic elements. Although plant extracts have an outstanding nutritional and phytochemical profile, more in-depth clinical research and effective commercialization of P. guajava-based processed food are still required to confirm their usefulness. In addition, using P. guajava to synthesize nanoparticles for industrial applications has untapped scientific potential that calls for more examination and exploration.